Acute Stent Thrombosis Associated with Eptifibatide-Induced Profound Thrombocytopenia - Amer Aljundi; Alaa Rahhal; Wafer Dabdoob (Case Reports in Cardiology)
Background. Eptifibatide is an inhibitor of the platelet glycoprotein (GP) IIb/IIIa receptor that is commonly used in patients undergoing percutaneous coronary intervention (PCI). Case. We describe a case of a 62-year-old female patient admitted with acute ST-elevation myocardial infarction (STEMI) treated by primary coronary intervention (primary PCI) with a drug-eluting stent placement. She developed profound thrombocytopenia within 8 hours of first administration of eptifibatide and subsequent acute stent thrombosis next day. Other causes of thrombocytopenia were excluded and intravascular ultrasound (IVUS) showed good stent expansion and opposition to the coronary wall. Platelet count gradually returned to normal after discontinuation of eptifibatide. Conclusion. Although Eptifibatide has been associated with the development of thrombocytopenia, to the best of our knowledge, this is the first case report in the medical literature that associates acute stent thrombosis and eptifibatide-induced thrombocytopenia.